2015
DOI: 10.1002/jemt.22604
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional structure of the lingual papillae in three species of South American Camelids: Alpaca, guanaco, and llama

Abstract: The aim of this study was to compare the anatomical and functional characteristics of the lingual papilla among the Camelidae. For this purpose, tongues of alpaca, guanaco, and llama were used. Numerous long and thin filiform papillae were located in the median groove and none were detected on the rest of the dorsal surface of the lingual apex in alpaca. Secondary papillae originated from the base of some filiform papillae on the ventral surface of alpaca tongue. The bases of some filiform papillae of the late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 32 publications
9
27
0
Order By: Relevance
“…In the previous studies, it is reported that dorsal faces of all papillae vallatae are flat (Ates, Akaydin Bozkurt, Kozlu, Alan, & Düzler, 2013;Can et al, 2016;Erdogan et al, 2016;Erdogan & Perez, 2014;Jackowiak & Godynicki, 2004;Yoshimura et al, 2013;Zheng & Kobayashi, 2006). However, circular extensions were determined on the tongues of wolves that were varying between 10 and 14 in number.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the previous studies, it is reported that dorsal faces of all papillae vallatae are flat (Ates, Akaydin Bozkurt, Kozlu, Alan, & Düzler, 2013;Can et al, 2016;Erdogan et al, 2016;Erdogan & Perez, 2014;Jackowiak & Godynicki, 2004;Yoshimura et al, 2013;Zheng & Kobayashi, 2006). However, circular extensions were determined on the tongues of wolves that were varying between 10 and 14 in number.…”
Section: Discussionmentioning
confidence: 97%
“…Conic papilla filiformes determined that on the anterior two‐thirds of the dog tongue are curved posteriorly and these are exhibited seconderary conical projections (Singh, Boshell, Steflik, & McKinney, ). In a study carried out on South American camelids, it is expressed that these papillae are only seen on the median line of dorsal face of the tongues and are seen in a shape of a hook (Erdogan, Arias, & Perez, ). In another study about merino sheep, it was reported that papillae filiformes were placed on apex and corpus and rarely observed in lateral region of the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…The lingual median sulcus is a characteristic morphological feature in some mammals (Iwasaki et al., ; Jackowiak and Godynicki, ; Nasr et al., ; Abumandour and El‐Bakary, ; Erdogan and Perez, ; Erdogan et al., ). In contrast, this groove is absent in some mammalian species as noted in the current study and by Emura et al.…”
Section: Discussionmentioning
confidence: 99%
“…There is species‐specific in the characteristic appearance of the lingual papillae from; size, shape, number, distribution, nomenclature and orientation between different mammalian species (Abumandour and El‐Bakary, ; Erdogan et al, ). These species differences depend on dissimilarities in types of food, feeding habits and handling of food materials in mouth (Iwasaki, ; Abumandour and El‐Bakary, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation